Comparison of the Levator Hiatal Area - Juniarto, Muhammad E; Moegni, Fernandi (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To determine the relationship of the levator hiatal area among nulliparous, primiparous, and multiparous women so that we can assess the prevalence of avulsion. Method: A cross-sectional study design was used by evaluating the transperineal ultrasound results of all nulliparous, primiparous, and multiparous women in the Obstetrics and Gynecology Clinic of Dr. Cipto Mangunkusumo hospital from May to December 2015. We analyzed the data through SPSS using one way ANOVA to compare the levator hiatal dimension among the groups of women during Valsava maneuver and at rest. Result: There were significant differences in levator hiatal area among nulliparous, primiparous, and multiparous women during Valsalva maneuver and at rest, which the mean (SD) was 22.26 (5.45) cm2 (p=0.028) and 10.70 (2.26) cm2 (p=0.012), respectively. Levator ani muscle avulsion was occurred in 1 out of 46 (2.2%) women from the primiparous and multiparous group. onclusion: There are significant differences in levator hiatal area during Valsalva and at rest among the groups. [Indones J Obstet Gynecol 2016; 4-4: 208-211] Keywords: avulsion, levator hiatal area, multiparous, nulliparous, primiparous